2014
DOI: 10.1128/jb.01086-13
|View full text |Cite
|
Sign up to set email alerts
|

The Stringent Response Modulates 4-Hydroxy-2-Alkylquinoline Biosynthesis and Quorum-Sensing Hierarchy in Pseudomonas aeruginosa

Abstract: cAs a ubiquitous environmental organism and an important human pathogen, Pseudomonas aeruginosa readily adapts and responds to a wide range of conditions and habitats. The intricate regulatory networks that link quorum sensing and other global regulators allow P. aeruginosa to coordinate its gene expression and cell signaling in response to different growth conditions and stressors. Upon nutrient transitions and starvation, as well as other environmental stresses, the stringent response is activated, mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 76 publications
6
57
0
Order By: Relevance
“…Because rhamnolipids might act as a wetting agent for bacteria to overcome surface tension to facilitate their movement across the moist surface (Caiazza et al, 2005), the decreased rhamnolipid synthesis (Fig. S4) might Similarly, Schafhauser et al showed that P. aeruginosa ppGpp deficiency results in impaired las and rhl system and the reduced production of rhamnolipid and elastase (Schafhauser et al, 2014). In addition, Nguyen and Schafhauser et al also found that the P. aeruginosa ppGpp-null (ΔSR) mutant displayed increased levels of HHQ, PQS, pqsA and pqsR (Nguyen et al, 2011;Schafhauser et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Because rhamnolipids might act as a wetting agent for bacteria to overcome surface tension to facilitate their movement across the moist surface (Caiazza et al, 2005), the decreased rhamnolipid synthesis (Fig. S4) might Similarly, Schafhauser et al showed that P. aeruginosa ppGpp deficiency results in impaired las and rhl system and the reduced production of rhamnolipid and elastase (Schafhauser et al, 2014). In addition, Nguyen and Schafhauser et al also found that the P. aeruginosa ppGpp-null (ΔSR) mutant displayed increased levels of HHQ, PQS, pqsA and pqsR (Nguyen et al, 2011;Schafhauser et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…The P. aeruginosa ΔRS mutant, which is deficient in the synthesis of ppGpp, is severely attenuated in virulence in chronic infection models of D. melanogaster (Vogt et al, 2011). The secretion of virulence factors, such as pyocyanin, elastase, protease, siderophores (Vogt et al, 2011), rhamnolipid (Schafhauser et al, 2014) and swarming and twitching were impaired in the ΔRS mutant compared with wild-type P. aeruginosa (Vogt et al, 2011), suggesting that ppGpp might play a role in promoting the production of bacterial virulence factor. In addition, reports showed that ppGpp is required for biofilm formation in Streptococcus mutans (Lemos et al, 2004), and ppGpp might decrease the sensitivity of biofilm to the treatments of antibiotics (Nguyen et al, 2011) and anti-biofilm peptide (de la Fuente-Nunez et al, 2014)(de la Fuente-Nunez et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, it was demonstrated that during growth under nutrient-restricted conditions the ⌬rpoN mutant downregulates the expression of pqs signaling (70). Low metabolic activity and stressed environmental conditions are connected with the increase in the levels of the alarmone ppGpp, a regulator of the stringent response, which is involved in the regulation of QS systems, the nitrogen stress response, and antibiotic tolerance (5,8,71,72) and is essential for sustaining the survival of the cells. Therefore, we postulate that another level of RpoN regulation is mediated through ppGpp.…”
Section: Discussionmentioning
confidence: 99%
“…Gene induction studies in Pseudomonas aeruginosa have shown that signal integration from nutrient starvation, induction of RpoS (a stationary-phase sigma factor) and the stringent response, and cell density-dependent autoinducer accumulation is necessary for induction of QS-controlled genes (14,35,64,65). QS genes from members of the Rhizobiales, such as R. palustris, Sinorhizobium meliloti, A. tumefaciens, and M. extorquens, generally respond to nutrient presence or deprivation (13,41,45,52,66).…”
Section: Discussionmentioning
confidence: 99%